Cost-effectiveness of a multi-professional case management experiment in Finnish labor market services - Jan Klavus; Sami Ylistö; Leena Forma; Jussi Partanen; Pekka Rissanen; Mikko Mäntysaari (University of Oslo, 2020)
The study undertook an economic evaluation of a multi-professional case man-agement intervention targeted at long-term unemployed Finns. The cost-effectiveness outcome of the intervention was analyzed in a matched case-control study framework involving a six-month follow-up. Effectiveness was measured by standardized quality of life indicators, and an indicator measuring personal capabilities. Individual level costs were derived from health and social services utilization data. Cost-effectiveness of the intervention was examined in relation to services as usual. The studied labor market intervention was associated with a positive change in the selected quality of life indicators; physical and psychological quality of life improved in the intervention group. Cost-effectiveness in physical quality of life was attained at a willingness to pay of EUR 500 - 700 per effectiveness unit, while cost-effectiveness in psychological quality of life required incremental costs exceeding EUR 1,600. The intervention had no discernible effect on personal capabilities. The study demonstrated that favorable improvements in quality of life could be attained by a rather 'light' and moderate-cost service concept. Such well-being improvements may enhance the preparedness for re-employment of individuals with a prolonged unemployment history. However, a longer follow-up of the labor market intervention would be needed to examine the long-term effects on quality of life and employment. Published: Online October 2020.